Response Of Natural Zpt Generation Of Green Bean Sprouting Extract And Plant Media On The Growth Of Lemon Orange ( Citrus Limon L.) Plant Cuttings - Zulia, Cik; Lanna Reni Gustianty (Kirana Publisher (KNPub), 2023)
From March to May 2021, this study was carried out in the Asahan University research facility. This study's goal was to ascertain how administering natural ZPT green bean sprout extract and planting media affected the growth of lemon plant cuttings ( Citrus limon L.). It was a randomized block design that was used (RBD). The first of the two components in the factorial treatment design is the administration of ZPT natural green bean sprout extract (Z) at four levels: Z 0 = no immersion, Z 1 = one hour of immersion, Z 2 = two hours of immersion, and Z 3 = three hours of immersion. The second factor is how growing media (M) are treated, with M 0 being moss and topsoil and M 1 being cocopeat and topsoil, and M 2 being chaff charcoal and topsoil, at three different levels. The proportion of live cuttings (%), the number of days before shoots appeared (days), the shoot height (cm), the number of leaves (strands), and the length of the roots were the parameters measured (cm). Almost all of the observed parameters, with the exception of the age at which shoots developed from cuttings, did not respond significantly to the administration of natural PGR extract of mung bean sprouts, according to the data. While this was going on, the treatment of the planting medium had a very big impact on the parameters of root length and leaf count that had been measured. In the meantime, the treatment of the planting medium had a very substantial impact on the parameters of root length, number of leaves, and shoot height that were measured. The percentage of live cuttings and the age at which shoots first developed, however, did not appear to have any discernible effects. Citrus limon L. cutting growth was not significantly affected by the interaction between the response of administering natural PGR extract of green bean sprouts and planting media, according to all measured parameters.